Perspective of surface modification of CdTe single crystal substrate for creation of photosensitive barrier structures - Makhniy, V.P.; Skrypnyk, N.V.; Boyko, Yu.N. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2009)
Analyzed in this paper is the influence of various modifications of substrate surface in n-CdTe single crystals (laser, thermal and photothermal) on electric and photoelectric properties of diode structures based on them.